Pengaruh Kombinasi Aromaterapi Lemon dan Air Jahe pada Emesis Gravidarum - Kartikaningsih; Renita Rizkya Danti Renita; Indah Christiana (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Emesis gravidarum is common problem experienced by 50-90% of pregnant women, and 2% of these cases into hyperemesis gravidarum. One of the safe solutions to nausea and vomiting of pregnant women with non-pharmacological therapy of lemon aromatherapy and ginger drink. This study aims to test the effectiveness of a combination of lemon aromatherapy and ginger drink to reduce nausea and vomiting in pregnant women. This research method used quasy experiment, pre-post test control group design. Population was pregnant women at TPMB in Songgon District who experienced nausea and vomiting. This study used consecutive sampling inclusion criteria, 20 people for the treatment group and 20 people in the control group. Data analysis used the Wilcoxon Sign Rank Test. Before the intervention, the frequency of nausea and vomiting in the study subjects was high. However, after treatment, there was decrease in the frequency of nausea and vomiting. The results of data analysis show a value of P = 0.000, which states that P < 0.05, meaning that there is an effect of giving a combination of lemon aromatherapy and ginger drink on reducing emesis gravidarum in TPMB in the Songgon Banyuwangi sub-district area in 2021. Health workers can use non-pharmacological alternative therapy in the form of combination of lemon aromatherapy and ginger drink as a step to reduce and overcome symptoms of nausea and vomiting. In addition, there is an opportunity to conduct research as one of the safe solutions to overcome nausea and vomiting of pregnant women with other complementary therapies.